Physiological responses to starvation in European eel (Anguilla Anguilla): effect on haematological, biochemical, non specific immune parameters and skin structures. - G. CARUSO; G. MARICCHIOLO; V. MICALE; L. GENOVESE; R. CARUSO; DENARO, Maria Gabr. (Fish Physiology and Biochemistry, 2008)
The physiological effects of short-term starvation on some haematological, biochemical and non-specific immune response parameters together with the histological structure of the skin, were investigated in the European eel, Anguilla anguilla. Blood haemoglobin and haematocrit, serum glucose and cortisol, hemolysins, haemagglutinins, and lysozyme in the plasma, kidney and epidermal extract, were measured in fish after 31, 42 and 58 days of starvation, and compared to those of fed fish. Starvation did not affect haemoglobin and haematocrit values, while an increase in glucose and cortisol levels was found in starved eels by day 42. Haemolytic and haemagglutinating activities decreased in starved eels. On the other hand, starvation caused an increase in the lysozyme content in the epiderma extracts, while no significant variations were observed in kidney and plasma. On the whole, no major changes in metabolic, haematological and nonspecific immune parameters were observed when short-term (less than 2 months) starvation was applied to the European eel, suggesting an adaptive response to starvation, rather than a typical alarm– stress response, allowing this species to withstand food deprivation.